Contrast-enhanced ultrasound evaluation of the utero-placental perfusion in ewes - Santos, Victor José Correia [UNESP]; Del'Aguila-Silva, Priscila [UNESP]; Silva, Priscila [UNESP]; Gasser, Beatriz; Estrada, Cristhian Rene Vargas [UNESP]; Carneiro, Rafael Kretzer; Pavan, Letícia [UNESP]; Aires, Luiz Paulo Nogueira [UNESP]; da Cruz, Igor Cezar Kniphoff; Uscategui, Ricardo Andres Ramirez; Vicente, Wilter Ricardo Russiano [UNESP]; Silva, Luciano Andrade; et al. (Elsevier, 2023)
This study highlights the importance of blood circulation between mother and fetus for a healthy pregnancy and optimal lamb development. It addresses the challenges of studying blood flow in the utero-placental complex due to small vessel diameters and slow flow. To overcome these, the study utilized contrast-enhanced ultrasound technology (CEUS), which proved to be a safe and effective method for assessing blood flow in the uterus and placentomes of ewes. It reveals a distinct centrifugal and homogeneous perfusion pattern in the uterus and a homogeneous and centripetal pattern in placentomes, with no enhancement detected in the embryos or fetuses. The results, including Doppler and CEUS parameters, provide valuable insights into blood circulation during pregnancy and its developmental changes. It contributes to a better understanding of normal embryonic/fetal development in ewes throughout gestation.
Keywords: Microbubbles; Pregnancy; Sheep; Ultrasound